Electrocardiogram (ECG) Application for Checking Heart Conditions Based on Android - Eko Budi Setiawan; Muhammad Yasin Tahir (IJNMT (International Journal of New Media Technology), 2019)
Abstract— Based on Indonesia Health Research Data globally the number one cause of death is caused by cardiovascular diseases, namely heart and blood vessel function disorders such as Coronary Heart Disease, Heart Failure or Heart Disease, Hypertension and Stroke. In 2008 it was estimated that 17.3 million deaths were caused by cardiovascular disease, and more than 3 million of these deaths occurred before the age of 60 years where this age could have been prevented. With the advancement in technology, it is now needed tools/applications that can monitor heart conditions at any time and any time to prevent deaths caused by sudden heart attacks. The research method used is the QRS approach and use AD8232 to get ECG data. Where to prove the results of the research conducted are appropriate or not by comparing the real ECG data in the hospital with ECG data obtained from the results of the study. The results of testing the data collected in this study can be said that the data in the application built is almost matched with the data obtained from the test results using hospital tools, with a data matching percentage of 96% for QRS interval and 90% for RR interval. Index Terms— ECG, AD8232, QRS Interval, RR Interval.